Net Working Capital, Capital Expenditure, Leverage, Board Size, Dan Cash Holdings - Yanti, Madeline Vania Wijanto, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This study aims to analyze the effect of net working capital, capital expenditure, leverage, and board size on cash holdings with firm size and profitability as controlling variables. This study uses secondary data obtained from financial statement and annual report manufacturing firms listed on IDX for the period 2016-2019. Research method using multiple linear regression, which is tested using E-views dan SPSS. This study uses Generalized Least Square with random effect model in testing hypothesis. Samples are chosen based on purposive sampling method. There are 69 manufacturing company listed on IDX for the period 2016-2019 with total 276 data selected as samples. This study found that net working capital has a significant positive impact on cash holdings. Capital expenditure has negative and significant relation with cash holdings. On the other hand, leverage and board size were found to have no significant effect on cash holdings.